ADVERBIA DALAM BAHASA JEPANG DAN PADANANNYA DALAM BAHASA INDONESIA - Mariana Wouthuyzen (Sekolah Tinggi Bahasa Asing Yapari-ABA, 2021)
This aim of this writing is to analyze fukushi (adverbs) in Japanese language, especially about words in relation with the form, the use, and the meaning of fukushi. The writer shows that the fukushi of taihen, taisō, sōtō ni, makoto ni, totemo, zuibun, and hijō ni have either the same or similar meaning, but each usage is different. In addition, fukushi can be used to describe dōshi (verbs), keiyōshi (adjectives-i), and keiyōdōshi (adjectives-na). However, they can not become subjects, predicates, complements and conjugation. Fukushi can also be yogen or other fukushi so that it is similar with adverb in Indonesian language.